Prospecting agro-waste cocktail: supplementation for cellulase production by a newly isolated thermophilic B. licheniformis 2D55 - Kazeem, Muinat Olanike; Md Shah, Umi Kalsom; Samsu Baharuddin, Azhari; Abdul Rahman, Nor' Aini (Springer, 2017)
Bacteria isolated from thermophilic environment that can produce cellulase as well as utilise agro-waste biomass have a high potential for developing thermostable cellulase required in the biofuel industry. The cost for cellulase represents a significant challenge in converting lignocellulose to fermentable sugars for biofuel production. Among three potential bacteria examined, Bacillus licheniformis 2D55 (accession no. KT799651) was found to produce the highest cellulolytic activity (CMCase 0.33 U/mL and FPase 0.09 U/mL) at 18-24 h fermentation when grown on microcrystalline cellulose (MCC) as a carbon source in shake flask at 50 °C. Cellulase production process was further conducted on the untreated and NaOH pretreated rice straw (RS), rice husk (RH), sugarcane bagasse (BAG) and empty fruit bunch (EFB). Untreated BAG produced the highest FPase (0.160 U/mL), while the highest CMCase (0.150 U/mL) was supported on the pretreated RH. The mixture of untreated BAG and pretreated RH as agro-waste cocktail has remarkably improved CMCase (3.7- and 1.4-fold) and FPase (2.5- and 11.5-fold) compared to the untreated BAG and pretreated RH, respectively. The mechanism of cellulase production explored through SEM analysis and the location of cellulase enzymes of the isolate was also presented. Agro-waste cocktail supplementation provides an alternative method for an efficient production of cellulase.